2006
DOI: 10.1186/1471-2164-7-323
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of noncoding microsatellites in plants: implication for gene regulation

Abstract: BackgroundMicrosatellites are extremely common in plant genomes, and in particular, they are significantly enriched in the 5' noncoding regions. Although some 5' noncoding microsatellites involved in gene regulation have been described, the general properties of microsatellites as regulatory elements are still unknown. To address the question of microsatellites associated with regulatory elements, we have analyzed the conserved noncoding microsatellite sequences (CNMSs) in the 5' noncoding regions by inter- an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 48 publications
1
59
1
Order By: Relevance
“…And we found that the introns didn′t contain more hexanucleotide P-SSRs than exons, which was inconsistent with previous reports [2]. It has been reported that CDSs are preferentially selected with tri- and hexanucleotide SSR motifs [3, 28,30,43,46], which can reduce potential translational frameshift mutations [47]. This evidence can help to explain why tri-fold nucleotide SSR motifs are more frequent in CDSs than other genomic regions.…”
Section: Discussioncontrasting
confidence: 87%
“…And we found that the introns didn′t contain more hexanucleotide P-SSRs than exons, which was inconsistent with previous reports [2]. It has been reported that CDSs are preferentially selected with tri- and hexanucleotide SSR motifs [3, 28,30,43,46], which can reduce potential translational frameshift mutations [47]. This evidence can help to explain why tri-fold nucleotide SSR motifs are more frequent in CDSs than other genomic regions.…”
Section: Discussioncontrasting
confidence: 87%
“…For example, SSRs in coding regions that result in amino acid changes can cause either loss or gain of function, SSRs in the 5′UTR can affect gene transcription or translation, SSRs in the 3′UTR can be responsible for gene silencing or transcription slippage, and SSRs in introns might act as transcriptional enhancers of gene expression. 8,32,40 Previous study that phenylalanine ammonia-lyase (PAL) transcripts have been localized to develop xylem cells in aspen ( P. tremuloides ) stem, was consistent with its involvement in lignin biosynthesis. 41 This report supported the identification of a single-marker non-coding association in PtoPAL 2 that explained 4.6% of the phenotypic variation in lignin content (Table 5).…”
Section: Discussionmentioning
confidence: 65%
“…The expansion and contraction of microsatellite repeats in the 5′ UTRs of genes have significance in regulating gene expression for many traits including amylose content in rice, 71 quality protein in maize 72 and light and salicylic responses in Brassica . 73 These findings thus inferred the significant correlation between the number of microsatellite repeat units in the different sequence components (functional domain and 5′ UTR) of seed weight/size trait-specific TFFDMS and TFGMS associated TF genes and their differential expression in the genes preferentially with regard to seed development in contrasting chickpea genotypes. Understanding the adaptive and evolutionary significance of such TFFDMS and TFGMS repeat expansion/contraction in the functional domain and 5′ UTRs of TF genes, respectively, is of relevance that needs further systematic experimentation by assaying a large number of contrasting chickpea genotypes of different tissues and/or stages (embryogenesis to maturation) of seed development.…”
Section: Resultsmentioning
confidence: 76%